Effect of Debt and Export on GDP of Nepal: an Empirical Analysis - Karmacharya, Nabindra Lal (Khwopa Journal, 2023)
This study aims to investigate the intricate relationship between Nepal's Gross Domestic Product (GDP), total debt, and export. Nepal, as a developing nation, faces numerous economic challenges, making it imperative to understand the dynamics of these key economic indicators and their interrelation. This study applies quantitative research methods, including statistical analysis, to examine the long-term trends, patterns, and causal relationships among these variables. The research begins by providing an overview of Nepal's economic landscape, highlighting its reliance on export-oriented industries and the significant impact of external debt on the national economy. A thorough literature review is conducted to identify existing theories and empirical studies related to GDP, total debt, and export, providing a foundation for the subsequent analysis. The study employs time-series data provided by NRB database, covering a significant period of 1975 to 2020 AD, to construct a robust empirical framework. Various econometric techniques, such as correlation analysis, regression models, normality test, are applied to explore the relationship between Nepal's GDP, total debt, and export using EViews 10. The findings of the study contribute to a deeper understanding of the economic dynamics in Nepal. The results reveal important insights into the impact of total debt on GDP growth and the role of export in driving economic development. Furthermore, the study uncovers potential feedback effects and spillover mechanisms among these variables, providing policymakers with valuable information for formulating effective economic strategies and debt management policies. Overall, this study sheds light on the complex relationship between Nepal's GDP, total debt, and export, offering valuable insights into the country's economic performance.